Synthesis of Substituted Cinnamido Linked Quinazolinone Congeners as Potential Anticancer Agents via Mitochondrial Dependent Intrinsic Apoptotic Pathway - Manasa, Kesari L.; Saifi, Mohd A.; Tangella, Yellaiah; Godugu, Chandraiah; Alvala, Mallika (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: The synthesis of novel heterocyclic scaffolds with amide functionality is a key research area due to their plethora of medicinal applications. The present study aims to explore the synthesis of new cinnamido linked quinazolinone congeners and their potential as anticancer agents. Methods: Cytotoxicity evaluation, Cell cycle analysis, JC-1 staining, ROS, Annexin V assays, AO/EB, DAPI nuclear staining, Colony-forming assay and Western blot analysis. Results: Among the synthesized compounds, 5eb and 5fc have shown promising cytotoxic activity with an IC50 value of 3.89±1.01μM and 4.05±0.62μM against HeLa cell lines. The flow-cytometry analysis demonstrated that the compound 5eb arrested the sub-G1 phase of the cell cycle and induced apoptosis. Furthermore, the compound 5eb triggered the collapse of mitochondrial membrane potential (ΔΨm), which was assessed by JC-1 staining and also induced the generation of Reactive Oxygen Species. An increase in the expression of proapoptotic proteins such as Bax, p53, cleaved PARP and cleaved caspase-3 by 5eb confirmed the activation of the mitochondrial-dependent intrinsic apoptosis pathway. Conclusion: Our results suggest that compound 5eb and 5fc of cinnamido linked quinazolinone derivatives could serve as potential leads in the development of novel chemotherapeutic agents.
Keywords: cytotoxicity